Bone Marrow Mesenchymal Stromal Cells: Identification, Classification, and Differentiation - Gao, Qianmin; Wang, Lipeng; Wang, Sicheng; Huang, Biaotong; Jing, Yingying; Su, Jiacan (Frontiers in Cell and Developmental Biology, 2022)
Bone marrow mesenchymal stromal cells (BMSCs), identified as pericytes comprising the hematopoietic niche, are a group of heterogenous cells composed of multi-potent stem cells, osteochondral and adipocyte progenitors. Nevertheless, the identification and classification are still controversial, which limits the application. Recent years by lineage tracing and single-cell sequencing several new subgroups of BMSCs have been identified and their roles are clarified in normal physiological and pathological conditions. Key regulators and mechanisms controlling BMSCs fate are being revealed. Cross-talks among subgroups of bone marrow mesenchymal cells have been demonstrated. In this review, we focus on the recent advances in identification and classification of BMSCs, which provides important implications for clinical applications.